"Identity is in the raw material." Pedagogical practice by instructor Juan Guillermo Peláez, a commitment to ancestral knowledge and practical tradition - Simbaqueba, Juan
This article presents the work carried out by Professor Juan Guillermo Peláez, who from his pedagogical practice establishes links between learning, ancestral knowledge and training for work, rescuing culture, taking it to the present and projecting it into the future; all from a symbiotic relationship with the local artisans of the city of Santa Marta and their treatment of raw materials.